1952
DOI: 10.1039/jr9520003579
|View full text |Cite
|
Sign up to set email alerts
|

682. Studies in co-ordination chemistry. Part XIV. The magneto-chemistry of simple and complex fluorides of transition metals

Abstract: Studies in Co-ordination Chemistry. Part X f V . 3579 682. Studies in Co-ordination Chemistry. Part X U . * The Magneto-chemistry of Simple and Complex Fluorides of Transition * Part XIII, preceding paper. UNIVERSITY COLLEGE, LONDON. UNIVERSITY CHEMICAL LABORATORY, CAMBRIDGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 0 publications
10
64
0
Order By: Relevance
“…because in their structure the [FeF 5 9 H20] 2-complex ion has a lower symmetry than cubic. For some of these substances, with M = Fe 3 § V 3 § Cr 3 § Mn 2+, early studies were reported in the literature [20][21][22][23]. We have already shown [24] that the [CrF 5.…”
Section: Introductionmentioning
confidence: 84%
“…because in their structure the [FeF 5 9 H20] 2-complex ion has a lower symmetry than cubic. For some of these substances, with M = Fe 3 § V 3 § Cr 3 § Mn 2+, early studies were reported in the literature [20][21][22][23]. We have already shown [24] that the [CrF 5.…”
Section: Introductionmentioning
confidence: 84%
“…A compound with the empirical formula PdF 3 was originally proposed to contain Pd(III) [16,17], but was subsequently shown to by more appropriately formulated as Pd 2+ [PdF 6 ] 2− and contain Pd(II) and Pd(IV) [18,19]. The polyatomic anions PdF 4 − and PdF 6 3− have been prepared by solid-state synthesis [20-22].…”
Section: Mononuclear Pd(iii) Chemistrymentioning
confidence: 99%
“…The distance between P d and F ions is equal to 2.04 A [18]; PdF, has be reported to have an effective moment 2 . 0 5~~ [19] a t room temperature. Nyholm and Sharpe [19] explained the magnetic moment by the t&e& electron configuration.…”
Section: Trivalent Halides Of Ni Pd and Ptmentioning
confidence: 99%
“…0 5~~ [19] a t room temperature. Nyholm and Sharpe [19] explained the magnetic moment by the t&e& electron configuration. Then Bartlett and Rao [20] have shown that the compound apparently has the composition Pd2+[Pd4+F,] in whikh Pd2+ is assigned the high-spin configuration t$eg.…”
Section: Trivalent Halides Of Ni Pd and Ptmentioning
confidence: 99%